ELUCIDATING THE IMPACT OF ELECTRONIC WORD OF MOUTH TO THE INTENTION TO USE LINKEDIN FOR ASEAN JOBSEEKERS: MODERATING ROLE OF GENDER - Vincentius Nuring Saptadi Suryo; Mone Stepanus (Jurnal TAM (Technology Acceptance Model), 2023)
LinkedIn is one of the most popular e-recruitment tools for job applicants. Although previous studies had explored the effectiveness of LinkedIn, the underlying cause of jobseekers' intention to use LinkedIn is still under-researched. This study examines the impact of Electronic Word of Mouth (eWOM) to the behavioral intention (BI) of jobseekers to use LinkedIn, using the Technology Acceptance Model (TAM) as the framework. The Partial Least Square Structural Equation Modelling (PLS-SEM) was applied to analyze 431 samples of ASEAN Jobseekers via SmartPLS 3. Findings show that eWOM positively influences the perceived ease of use (PEOU), Perceived Usefulness (PU), and Attitude (AT) of jobseekers, which consequently positively impacts the jobseekers' behavioral intention (BI) to use LinkedIn. The mediating role of PEOU, PU., and AT was also examined and shows that the three variables partially mediate the relationship between eWOM and BI. Theoretically, this study uncovers the significance of eWOM in new technology acceptance. Practically, managers can use this information to increase positive eWOM of their company’s LinkedIn profiles to attract more decent talents to the company. To the authors' knowledge, this study is one of the first investigations into how external variables influence the TAM Model in e-recruitment which uses regional samples instead of specific country-wide samples.